THE SYMBOLIC USE OF PLACES IN ZEYNO'NUN OĞLU AND KALP AĞRISI NOVELS - Mehmet Emin PURÇAK (Fırat University, 2019)
Halide Edip was one of the most important woman writer of Turkish literature. She was born in an era of huge difficulties experienced by the Turkish society and she herself experienced lots of difficulties, too. She had a good education with the help of her family. Early on, she felt great admiration to America and the UK. But because of the West's attempts to occupy the Ottoman and Turkey, she kept away from West. Her works were mostly on East-West civilizations and Turkey's development problems. Although Halide Edip didn't reject West civilization completely, she opposed a full submission to become dependent on them. According to her, Turkey should create a synthesis from Eastern and Western civilizations. There are two novels of her '' Kalb Ağrısı'' and '' Zeyno'nun Oğlu'' in which she committed her ideas. In these two novels she worked on how Turkey should approach East and West civilizations by installing the symbolic meanings to cities.